PENYELESAIAN PERKARA DILUAR PENGADILAN(RESTORATIVE JUSTICE) TERHADAP TINDAK PIDANAKEKERASAN DALAM RUMAH TANGGA - Matsani, (2020)
Violent conflict in the household (domestic violence) is a very common case in the household phase and becomes a sensitive issue if not handled carefully. This research was conducted to find out how the legal basis for mediating the resolution of KDT cases outside the court; 2) What is the form and process of resolving cases of violence outside the court of households used by the parties; and 3) What factors hinder the success of the resolution of cases of domestic violence outside the court. This research method uses a normative juridical approach which is to study the legislation or law conceptualized as a rule or norm in handling domestic violence conflicts. The results of this study can be explained that the positive law of Indonesia in principle is not possible for settlement outside the Court, although in certain cases governed the settlement of cases outside the trial as in the resolution of domestic violence. Settlement of domestic violence through channels outside the court can be done in 3 (three) ways, namely: 1) Disputing Parties Settle Their Own Cases Without the Help of a Third Party as an Intermediary (Mediator); 2) Disputing Parties Ask For Help For Their Families To Be Settled (Mediated); and 3) Voluntary Dispute Agrees Agree to Come Ask for Community Leaders to become Mediators. There are several factors that become obstacles in the implementation of restorative justice, especially for the resolution of domestic violence, namely: 1) Legal substance that has not accommodated the implementation of restorative justice in full; 2) Law enforcers who have not optimally implemented existing regulations and are still behaving rigidly, and the culture of law / community participation has not been maximized; 3) Lack of regulation making that accommodates all provisions regarding the handling of domestic violence cases through a restorative justice approach, outreach to all law enforcement officials and the public; and 4) Coordination between law enforcement officers, and changing the paradigm of law enforcement officials from a retributive and restitutive justice approach to restorative justice has not yet been fully achieved.